System-level effects of increased energy efficiency in global low-carbon scenarios: A model comparison. (May 2022) - Dalla Longa, Francesco; Fragkos, Panagiotis; Pupo Nogueira, Larissa; van der Zwaan, Bob
Highlights: We model the global effects of enhanced energy efficiency in well-below-2 °C scenarios. We systematically compare the projections of two integrated assessment models. Increasing energy efficiency may lead to substantial long-term economic benefits. Carbon price and CCS use may decline by, respectively, 10–15% and 13–90%. The additional system costs needed to achieve climate targets may become 6–30% lower. Abstract: Supporting investments in energy efficiency is considered a robust strategy to achieve a successful transition to low-carbon energy systems in line with the Paris Agreement. Increased energy efficiency levels are expected to reduce the need for supply-side investments in controversial technologies, such as carbon dioxide capture and storage (CCS) and nuclear energy, and to induce a downward push on carbon prices, which may facilitate the political and societal acceptance of climate policies, without adversely affecting living comfort and sustainable development. In order to fully reap these potential benefits, economies need to design policy packages that balance emission reduction incentives on both the demand and the supply side. In this paper we carry out a model-comparison exercise, using two well-established global integrated assessment models, PROMETHEUS and TIAM-ECN, to quantitatively analyze the global system-level effects of increased energy efficiency in the context of ambitious post-COVID climate change mitigation scenarios. Our results confirm the expected benefits induced by higher energy efficiency levels, as in 2050 global carbon prices are found to decline by 10%–50% and CO2 storage from CCS plants is 13%–90% lower relative to the "default" mitigation scenarios. Similarly, enhanced energy efficiency reduces the additional average yearly system costs needed globally in 2050 to achieve emission reductions in line with the Paris Agreement. These additional costs are estimated to be of the order of 2 trillion US$ – or 1% of global GDP – in a well-below-2 °C scenario, and can be reduced by 6–30% with the adoption of higher energy efficiency standards. While the two models project broadly consistent future trends for the energy mix in the various scenarios, the effects may differ in magnitude due to intrinsic differences in how the models are set up and how sensitive they are to changes in energy efficiency and emission reduction targets.